PWE-205 Meat and the risk of pancreatic cancer: a prospective cohort study (EPIC-NORFOLK) using data from food diaries. (22nd June 2015) - Beaney, A; Banim, PJ; Luben, R; Khaw, K-T; Hart, AR
Abstract : Introduction: Processed, red and white meat intake may be involved in the aetiology of pancreatic cancer as they can contain carcinogens including nitrosamines, which may influence the natural history of the cancer at different ages. The data from epidemiological studies are conflicting, possibly due to lack of generalisability and inaccurate measures of diet. We investigated associations between processed, red and white meat intake and pancreatic cancer, for the first time using data from 7-day food diaries (7-DFDs), the most accurate questionnaire-based nutritional assessment. Method: 23, 658 participants recruited into the EPIC-Norfolk Study completed 7-DFDs and were followed up over 17 years to identify incident cases of pancreatic cancer. Meat intakes were divided into quintiles and compared with a sample of 3970 controls. Hazard ratios (HR) were calculated for developing pancreatic cancer for each quintile and for trends across quintiles, adjusted for age, sex, smoking, diabetes, and energy intake. A sub-group analysis was performed in participants younger and older than 60 years at recruitment. Results: During follow-up, 86 participants (0.36%) were diagnosed with pancreatic cancer (56% women). The median age at diagnosis was 73.4 years with a median survival of 4 months (inter-quartile range= 2–7 months). In the whole cohort, there were no associations with any quintiles of processed, red or white meats or for trends across quintiles. However, in participants younger than 60 years at recruitment, all quintiles of processed and red meat intakes were borderline significantly positively associated with risk (Q1 vs Q5, HR=3.73, 95% CI=0.95–14.66, p = 0.06 and Q1 vs Q5, HR=4.62, 95% CI=0.96–22.30, p = 0.06) respectively, with trends across quintiles for both (HRtrend =1.37, 95% CI=1.04–1.82 and HRtrend =1.33, 95% CI=1.00–1.77). For participants older than 60, there were no significant effects for either processed or red meats. For white meat, there was a positive association for all ages in quintiles two (HR=2.44, 95% CI=1.12–4.91) and four (HR=2.47, 95% CI=1.25–4.91), but no trend. There were no associations for white meat intake in those younger than 60 but the effects remained if older than 60. Conclusion: The findings suggest that processed and red meats may be involved in the aetiology of pancreatic cancer. As the associations are related to consumption before the age of 60 years, these meats may influence the development of precursor lesions for pancreatic cancer, such as pancreatic intraepithelial neoplasia (PanINs). The effects of white meat are uncertain. Processed and red meat intakes should be measured in aetiological studies, and reducing intake could reduce the incidence of pancreatic cancer. Disclosure of interest: None Declared.